2010
DOI: 10.1271/bbb.100040
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Relationship between Changes in Lactic Acid Bacterial Cell Components and Stimulation of IL-12 Production under Salt-Stressed Conditions

Abstract: One hundred and seventeen strains of plant origin lactic acid bacteria were observed to have interleukin (IL)-12 production-inducing activities using mouse peritoneal macrophages. Pediococcus pentosaceus (KKM122) was chosen for its stable and strong IL-12 production-inducing activity. There was no significant difference in IL-12 activity induced by the KKM122 strain grown in culture conditions of 0% and 6% NaCl. The cell wall components of cells grown in 6% salt condition, however, significantly induced lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…P. pentosaceus also has immunomodulatory effects. Earlier studies reported that P. pentosaceus induces interferon-γ and interleukin (IL)-12, and suppresses IL-4 in mouse spleen cells or peritoneal macrophages (Igarashi, 2010;Jonganurakkun et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…P. pentosaceus also has immunomodulatory effects. Earlier studies reported that P. pentosaceus induces interferon-γ and interleukin (IL)-12, and suppresses IL-4 in mouse spleen cells or peritoneal macrophages (Igarashi, 2010;Jonganurakkun et al, 2008).…”
Section: Introductionmentioning
confidence: 99%